Polarization domain splitting and incoherently coupled dark-bright vector soliton formation in single mode fiber lasers - Hu, Xiaonan (2022)
We have experimentally investigated the polarization dynamics of a weakly birefringent cavity single mode fiber laser under different laser operation conditions. We show features of polarization domain formation, domain splitting, and domain shaping into dark-bright vector solitons under incoherent cross-polarization coupling.